Sosialisasi dan Pelatihan Mangrove di Klabinain Kabupaten Sorong - Prabawati, Ratna; Fitriani, Anis Alfian (Jurnal Abdimasa Pengabdian Masyarakat, 2024)
Mangroves are an ecosystem that exists between land and sea environments. Currently, urban areas are increasing, so many mangrove forests are starting to be cut down. thus having a vulnerable impact on the mangrove environment and its surroundings. The role of mangroves for environmental sustainability is very important, so efforts are needed to overcome the problems faced, one of which is by producing lots of high quality mangrove seeds to preserve and maintain the mangrove ecosystem. Therefore, community service activities in producing mangrove seeds involve the community and institutions of the Sorong Muhammadiyah Education University, consisting of lecturers and students. This activity was carried out in 3 stages, namely preparation, implementation and evaluation. From the results of the activity, it can be concluded that the participants understand the importance of mangrove cultivation through making seedlings with the community and local officials.